SULTAN IN THE HISTORY OF TERNATE 1946-2002 - Hasyim, Rustam (JURNAL ILMU BUDAYA, 2016)
Politic participation of Ternate sultanate in local and national politic post independence to recent days brings important meaning to this writing. The reoccurance of past politic entity on that period explained as the wish of Ternate Sultanate to be more accomodated by means of institutional into formal government politic.Basically, this research is historical research concerning politic activities which is involving Sultanate by using historical method from heuristic to histography methods. This process requires analysis tools by using politics science concept to assist the extend study. The sources used in this research consisted of written and interview sources.This research conclude that politic participation of Sultanate in Ternate in local and national politic arena has experiencing tide and decrease as the impact of national politic system transformation. During President Soekarno era, Ternate Sultanate has opportunity in national politic field and the top of this opportunity is the appointment of Iskandar Djabir Syah, the 47th Ternate Sultanate, as Minister of Internal Affairs of East Indonesia State (NIT). In President Soeharto government period, the Sultanate elite is experiencing productivity by supporting Golkar Party. That support is able to bring them to manage their political career to become legislative members, academician, bureaucrats, politicians, press, and businessmen. Comes into reformation era, it presents wider space for Ternate Sultanate to express their existency and role. The arise of the 48th Ternate Sultan, Mudafar Syah, on his candidancy as Governor of North Maluku, as sultanate attempts in order to be constantly in its position as the authority holder in local domain, as their possession upon history claim and identity culture.The advantage of this research is capable to add and complete reference materials in Indonesian history documenting, particularly local history in North Maluku. This writing is expected to be able to give conteplation contribution for Ternate Sultanate elite and regional government in formulating political policies that are able to accomodate wider importance without according to certain ethnic importance.Keywords: Political History, Ternate Sultanate, National and Local Politic.